2000
DOI: 10.1093/nar/28.18.3517
|View full text |Cite
|
Sign up to set email alerts
|

Gradients in nucleotide and codon usage along Escherichia coli genes

Abstract: The usage of codons and nucleotide combinations varies along genes and systematic variation causes gradients in usage. We have studied such gradients of nucleotides and nucleotide combinations and their immediate context in Escherichia coli. To distinguish mutational and selectional effects, the genes were subdivided into three groups with different codon usage bias and the gradients of nucleotide usage were studied in each group. Some combinations that can be associated with a propensity for processivity erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 33 publications
1
62
0
Order By: Relevance
“…Nonsense errors have a number of different causes such as ribosome drop-off, improper translation of release factors, frameshifts, and even missense errors (Kurland 1992;Hooper and Berg 2000;Zaher and Green 2009). Direct estimates of the per codon nonsense error rates are rare, but those that do exist for Escherichia coli suggest that they are on the order of 10 À4 per codon (Manley 1978;Tsung et al 1989;Jorgensen and Kurland 1990).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonsense errors have a number of different causes such as ribosome drop-off, improper translation of release factors, frameshifts, and even missense errors (Kurland 1992;Hooper and Berg 2000;Zaher and Green 2009). Direct estimates of the per codon nonsense error rates are rare, but those that do exist for Escherichia coli suggest that they are on the order of 10 À4 per codon (Manley 1978;Tsung et al 1989;Jorgensen and Kurland 1990).…”
mentioning
confidence: 99%
“…As a result, selection against nonsense errors leads to the unique prediction that CUB should increase intragenically with codon position. Numerous researchers have shown either directly or indirectly that CUB does indeed increase with codon position in E. coli and other microorganisms (Hooper and Berg 2000;Qin et al 2004;Gilchrist and Wagner 2006;Stoletzki and Eyre-Walker 2007).…”
mentioning
confidence: 99%
“…We can see that the proteins could be preliminary separated into different subfamilies, i.e. Alpha herpesvirinae, Beta herpesvirinae and Gamma herpesvirinae (20,21 40), the codon usage bias in the UL31 -like genes of 49 reference species, especially the PRV is therefore, slightly high. If a specific gene is exposed to G + C compositional restriction for shaping the codon usage pattern, it will lie on a continuous curve, representing random codon usage (45).…”
Section: Molecular Phylogenetic Tree Of the Ul31-like Proteins In Prvmentioning
confidence: 99%
“…Further analysis found that synonymous codon usage pattern changed at distinct sites along a coding sequence (14), balances of strong versus weak base pair bonding (15,16), maintenance of DNA and RNA secondary structure (17), and translational efficiency and fidelity (6). Aujeszky's disease, which is provoked by the pathogenic factor of Pseudorabies virus (PRV) (also known as Suid herpesvirus 1,, is a regularly lethal disease with a global distribution that influences swine, mainly and other domestic and wild animals incidentally (18)(19)(20)(21)(22). PRV belongs to the genus Varicellovirus, subfamily alpha herpesvirinae, which is a swine alpha herpesvirus (20,(23)(24)(25)(26) …”
Section: Introductionmentioning
confidence: 99%
“…Several hypotheses attempt to explain how codon use mediates this effect, including but not limited to facilitating ribosomal pausing early in translation to optimize protein folding (13); adjusting mRNA secondary structure to optimize translation initiation or to modulate mRNA degradation; preventing ribosome stalling by coevolving with tRNA levels (6); providing a "translational ramp" for proper ribosome spacing and effective translation (14); and providing a layer of translational regulation for independent control of each gene in an operon (15). Additionally, codon use may impact translational fidelity (16), and the proteome may be tuned by fine control of the decoding tRNA pools (17). Although Quax et al (18) provide an excellent review of how biology chooses codons, systematic and exhaustive studies of codon choice in whole genomes are lacking.…”
mentioning
confidence: 99%